Substitution of whey protein by pea protein is facilitated by specific fractionation routes. (August 2021) - Kornet, Remco; Shek, Carol; Venema, Paul; Jan van der Goot, Atze; Meinders, Marcel; van der Linden, Erik
Abstract: In this study we investigated the effect of different aqueous fractionation processes on the suitability of pea protein isolates (PPI) to substitute whey protein isolate (WPI) in heat-set gels. We found that a milder fractionation process based on diafiltration was successful in substituting WPI, yielding similar gel strength (i.e. elastic modulus) at a range of concentrations. Three different pea protein isolates were analysed, one obtained using diafiltration (PPId), another obtained using isoelectric precipitation (PPIp), and a commercial one (PPIc) as a reference. The isolates PPIp and PPId contained mainly native proteins, whereas the proteins in PPIc were denatured. PPId had a protein solubility almost similar to that of WPI at pH 7, while PPIp and PPIc were less soluble. PPIp and PPIc had better thickening capacities, larger aggregate/particle sizes and higher viscosities compared to PPId. After heat-induced gelation all PPI's showed similar or higher gel strength than WPI between a 7–13 wt % protein concentration. Between 13 and 15 wt % PPId showed a similar gel strength compared to WPI. Above 15 wt % WPI formed the strongest gels. It was concluded that PPId can fully replace WPI up to protein concentrations of 15 wt %. For mixtures of WPI with the other PPI's, it turned out that up to half of the WPI could be replaced by any of the PPI's without compromising on gel strength. This makes us conclude that PPI is a suitable substitute for WPI in heat-set gels. Graphical abstract: Image 1 Highlights: Pea protein isolates (PPI) were obtained by different fractionation routes. Diafiltrated PPI approached the viscosity and solubility of whey protein isolate (WPI). The diafiltrated PPI also showed similar heat-set gel strength as WPI. Commercial and isoelectric precipitated PPI formed weaker and more heterogeneous gels. WPI dominated the rheological behaviour up to 50% substitution by any of the PPI's.